KAJIAN PENDAYAGUNAAN ZAKAT PRODUKTIF SEBAGAI ALAT PEMBERDAYAAN EKONOMI MASYARAKAT (MUSTAHIQ)PADA LAZISMU PDM DI KABUPATEN GRESIK - Syaiful, Syaiful; Suwarno, Suwarno (Universitas Muhammadiyah Surakarta, 2015)
This study aims to perform the evaluation and testing of the PerceptionKyai and Amil Zakat to good use and management cost that is based on Islamic law / law of Islam, mainly used for the economic empowerment of the community. In this research charity for people empowerment especially productive is to cultivate their entrepreneurial spirit. Society thus not only learn about the science of religion and general science course, but they must be equipped to live to work, namely by berwirasaha.With this charity also hopes the community continues to believe and are sure that the charity funds are used properly in accordance with the functions and resources of each charity. Because the potential is large enough charity in the city of Gresik, it needs to be extracted in a convincing way to muzakki about the benefits of charity, that charity is not only used for eight asnaf it, but could diijtihati become more efficient by empowering charity for the benefit of the economic boom.The methodology of this study is to use case studies dikmebngkan by Kayin, and data analysis using Maleong. Results from this study is that the community (mustahiq) and muzakki still lay with the model of productive utilization of zakat, zakat fund utilization is in accordance with the nature and origin of the zakat fund, Kyai opinion zakat should not be invested in any form, because Muhammad did not procrastinate charity, and the OKI Fiqh Council allow the use of zakat funds for investment.